La comunicación de las ciencias naturales en programas audiovisuales con destinatario infantil - Dra. María Agustina SABICH (Fonseca, Journal of Communication, 2023)
The paper proposes an approach to the modes of generic configuration in scientific outreach programs on Natural Sciences aimed at children. The corpus of analysis consists of two audiovisual series of the Argentinian Pakapaka channel that we define as «Biology program with a female host as protagonist» (Animapaka) and «Biology program with puppets» (El mundo animal de Max Rodríguez)